Implementing an opioid risk assessment telephone clinic: Outcomes from a pharmacist-led initiative in a large Veterans Health Administration primary care clinic, December 15, 2014–March 31, 2015. Issue 1 (2nd January 2016) - Jacobs, Sara C.; Son, Elizabeth K.; Tat, Christina; Chiao, Phillip; Dulay, Maya; Ludwig, Alison
ABSTRACT: Background : In response to the national epidemic of prescription opioid misuse and related adverse outcomes, two clinical pharmacists developed a telephone risk assessment clinic to promote safe opioid prescribing through a monthly assessment of patient medication use, aberrant behaviors, and side effects. Methods : A pilot group of five primary care providers and their patients with chronic nonmalignant pain on chronic opioid therapy, defined as having received prescription opioid medications for ≥90 days in the last 120 days, were identified. A risk assessment evaluation based on Veterans Health Administration/Department of Defense Clinical Practice Guideline for Management of Opioid Therapy for Chronic Pain was created. Factors assessed were receipt of non-San Francisco Veterans Administration Health Care System controlled substance prescriptions through California's prescription drug monitoring program, urine drug test (UDT) results, and aberrant behaviors. Pharmacist-recommended changes to regimen and provider response to recommendation were compiled. The pilot was conducted from December 15, 2014, to March 31, 2015. Results : Among 608 patients on chronic opioid therapy, 148 were assigned to pilot providers and 447 assessments were completed. Twenty-five (16.8%) patients had non-VA controlled substance prescriptions, of which 14 (56.0%) patients filled a non-VA controlled substance within 3 months of the start of pilot. Seventeen UDT results inconsistent with their prescribed regimens were identified from 12 patients (8.1%). Pharmacists recommended 66 changes to chronic opioid prescriptions in 48 patients (32.4%), including decreasing quantity of opioid(s) (33.3%), discontinuing chronic opioid therapy (22.7%), and delaying a fill (19.7%). Sixty-one of 66 (92.5%) pharmacist recommendations for regimen change were implemented by providers. Chronic opioid therapy was discontinued in 14 (9.5%) patients over the course of the pilot study. Conclusions : A pharmacist-led telephone risk assessment clinic improved adherence to clinical guidelines and changed opioid prescribing practices in more than one third of assessed patients.